Challenges and prospects in the uptake of citizen journalism by The Manica Post in Zimbabwe - Munyamana, Tafadzwa (Midlands State University, 2020)
The main aim of the research is to explore the challenges and prospects in the uptake of citizen journalism. The study also seek to explain the extent to which the uptake of citizen journalism by The Manica Post has promoted democratic participation of citizens and the contribution of the phenomenon to the production of news. The mainstream media have embraced the use of ICTs and this witnessed by the mainstream having their own social media pages and online websites where they publish articles. The uptake of citizen journalism has led to the creation of a converge newsroom and has helped in promoting democratic participation of citizens. The Manica Post has enjoyed the use of social media, although to a limited rate.